Bounds for α—Adjacency Energy of a Graph. Issue 1 (February 2021) - Shanmukha, B.; Shwetha, H. N; Manjunath, N
Abstract: Recently Nikiforov et.al [9] put forward the α —adjacencey energy of a graph G . In this paper, we continue the work on α —adjacencey energy and obtain bounds for this new parameter in terms of order, size and the first Zagreb index.